Pelatihan Intensif Perpajakan untuk Praktisi dan Mahasiswa dalam Rangka Peningkatan Kompetensi Pajak - Wening Estiningsih; Saripah Saripah; Yudi Budi Yuniarso; Ilham Teruna Bakti (Jurnal Ragam Pengabdian, 2025)
This Brevet A and B training program aimed to enhance participants' competence in understanding and fulfilling taxation obligations, both in theory and practice. The training was held over nearly four months and involved 76 participants from diverse backgrounds, including university students, MSME actors, and finance staff. The methods used included lectures, discussions, case studies, and hands-on SPT filing using the e-Filing platform. Evaluation results indicated a significant improvement in participants’ understanding, with average scores increasing from 58.2 to 85.6. A total of 96% of participants reported the ability to independently file taxes, and over 85% understood tax classification and income tax calculation. Other outcomes included increased tax compliance awareness and readiness for professional challenges. Technical and non-technical constraints were addressed through adaptive and responsive strategies. This training has proven to be an effective and replicable model for applied tax empowerment.